Description of Euroleuctra gen. nov., a new fossil genus of Leuctridae (Insecta: Plecoptera) in Eocene Baltic amber - Chen, Zhi-Teng (Zootaxa, 2018)
A new stonefly genus and species of the family Leuctridae, Euroleuctra gillesi gen. et sp. nov., is described and illustrated based on a well-preserved male specimen in the Eocene Baltic amber from Poland. The new genus is a new member of Leuctridae, exhibiting typical leuctrid diagnostic characters of the terminalia and wing venation. The new genus is also compared with related extant and extinct taxa.